Perbedaan Tingkat Kecemasan antara Siswa Program Akselerasi dengan Program RSBI di SMA Negeri 1 Yogyakarta - Deswandari, Alva Putri; ., Machmuroch; Wicaksono, Bagus (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Anxiety is a state of excessive or unjustified tense, characterized by feelings of worry, uncertain or fear. Teens especially students are susceptible to anxiety. Students of acceleration program are required to finish their study faster than any other programs, whereas students of RSBI program are required to use English actively. This study aims to find out the difference of anxiety levels between accelerated program students and RSBI program students at SMA Negeri 1 Yogyakarta. Methods: The study was an analytical observational research with cross sectional approach, conducted in Juli 2012 at SMA Negeri 1 Yogyakarta. Subjects were selected using different techniques, i.e. total sampling for students of acceleration program and cluster random sampling for students of RSBI program. Sixty-two subjects were asked to fill in T-MAS questionnaire; subjects were identified as anxious if their T-MAS scores â¥ 21. Data obtained were analyzed by Chi-square test using SPSS 17.0 for Windows. Results: The analyses showed a Chi-square value of 1,676 (p = 0,196). This study found no significant difference of anxiety levels between students of acceleration program and students of RSBI program at SMA Negeri 1 Yogyakarta. Conclusions: There was no difference of anxiety levels between students of acceleration programs and students of RSBI program at SMA Negeri 1 Yogyakarta. The finding highlights the need to conduct further research controlling other anxiety-related factors and using larger sample size. Keywords: Anxiety, Acceleration program, RSBI program